Biodiversity of meiofauna community in Da Nang bay and Son Tra peninsula, Da Nang province - Tu, Nguyen Dinh; Thanh, Nguyen Vu (Academia Journal of Biology, 2012)
The first result on meiofaunal community in the Da Nang bay and Son Tra peninsula was reported. Nine meiofaunal groups: Nematoda, Harpacticoids-Copepods, Turbelaria, Kinorhyncha, Polychaeta, Oligochaeta, Ostracoda, Halacaroidea and Insect larvae were recorded. Among them, Nematoda was the most predominant group with 96.36% of meiofaunal community of samples in term of individuals. Harpacticoids-Copepods followed with 1.84% and Polygochaeta and other groups occupied less than 1%. A total of 30 species marine nematodes belonging to 13 families of 3 orders were identified so far. The ratio of Nematoda/Copepoda (N/C) in all investigated stations was fluctuated between 16 and 78 according to the Warwick’s N/C ratio. With high diversity indexes, the environment quality seems to be good except two satations DN1 and DN3 that might be more disturbed.